2014
DOI: 10.1111/ggi.12295
|View full text |Cite
|
Sign up to set email alerts
|

Different obesity phenotypes, and incident cardiovascular disease and mortality events in elderly Iranians: Tehran lipid and glucose study

Abstract: Among the elderly population, the presence of MetS was necessary for exploring the risk of CVD events and its mortality; however, only the normal weight population with MetS had a significant risk for all-cause mortality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
(51 reference statements)
2
11
1
Order By: Relevance
“…19 The main finding in this study is that MHO subjects had an increased risk of incident CVD compared with MHNW individuals, which is consistent with several previous studies. 8,[20][21][22][23] However, the risk of incident CVD was not lower in MHO subjects when compared with MUO individuals, which differs from previous studies. 24,25 A meta-analysis of eight studies showed that the outcome of MHO was similar to that of MHNW 26 ; however, the studies that followed the subjects for more than 10 years found that patients in the MHO group had increased mortality and cardiovascular risks.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…19 The main finding in this study is that MHO subjects had an increased risk of incident CVD compared with MHNW individuals, which is consistent with several previous studies. 8,[20][21][22][23] However, the risk of incident CVD was not lower in MHO subjects when compared with MUO individuals, which differs from previous studies. 24,25 A meta-analysis of eight studies showed that the outcome of MHO was similar to that of MHNW 26 ; however, the studies that followed the subjects for more than 10 years found that patients in the MHO group had increased mortality and cardiovascular risks.…”
Section: Discussioncontrasting
confidence: 95%
“…The main finding in this study is that MHO subjects had an increased risk of incident CVD compared with MHNW individuals, which is consistent with several previous studies . However, the risk of incident CVD was not lower in MHO subjects when compared with MUO individuals, which differs from previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding KDM, our results are consistent with other reports on the significant predictive value of KDM for CVD and total mortality . Similar results have been noted for the role of KDM among older adults …”
Section: Discussionsupporting
confidence: 92%
“…Finally, 22 cohort studies met the inclusion criteria and were included, all of which were published in English 3–6 8–10 13 14 24–29 35–41. Eighteen studies evaluated CV events risk,4–6 8–10 13 14 24 26–29 35–38 41 and 11 studies evaluated all-cause mortality risk 3 4 8 13 24–26 35 38–40. The detailed information of included studies is presented in online supplementary file 1.…”
Section: Resultsmentioning
confidence: 99%